A composite conductive functional film and preparation method thereof

By designing composite conductive functional films in lithium-ion batteries, including lithium metal filling, organic film layer and high-temperature resistant sponge layer, the problem of energy density reduction in lithium-ion batteries is solved, and higher energy density and safety performance are achieved, and the The cost.

CN112712917BActive Publication Date: 2025-01-10CHONGQING JIMAT NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202110031875.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-01-11
Publication Date
2025-01-10
Estimated Expiration
2041-01-11

AI Technical Summary

Technical Problem

Lithium-ion batteries consume lithium ions during their first charge, resulting in a decrease in energy density, limiting the development of lithium-ion batteries.

Method used

A composite conductive functional film is designed, including a first film substrate layer, a second film substrate layer and a mixed layer arranged between the two, the mixed layer is filled with lithium metal and covered with organic film layer and high temperature resistant sponge layer. A metal layer is provided on the surface, and a dent is formed by etching and lithium metal is filled therein. An organic thin film layer is formed using organic lithium salts and lipid solvents, and finally a metal layer is added in the pressing step.

Benefits of technology

The energy density of lithium-ion batteries is improved, which is safer than the traditional lithium supplement method, reduces costs, and the same equipment plating a metal layer on the thin film substrate layer to achieve effective supplementation of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112712917B_ABST
    Figure CN112712917B_ABST
Patent Text Reader

Abstract

The present invention discloses a composite conductive functional film in the field of film manufacturing and a preparation method thereof, which overcomes the defect that the energy density of traditional lithium-ion batteries is reduced due to the consumption of lithium ions in the first charge, and can replenish the lithium ions consumed by the lithium-ion battery in the first charge. The film includes a first film substrate layer, a second film substrate layer and a mixed layer located therebetween, the mixed layer includes a film layer and a lithium supplement layer, a high temperature resistant sponge layer is provided between the mixed layer and the second film substrate layer, and a metal layer is provided on the surface of the first film substrate layer and the second film substrate layer; the preparation method includes the steps of preparing the first film substrate layer and the film layer, etching indentations, filling lithium metal, compounding a high temperature resistant sponge, compounding a second film substrate layer, adding a metal layer, and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of film manufacturing, and in particular to a composite conductive functional film for lithium ions and a preparation method thereof. Background Art

[0002] Batteries that can be recharged to activate the active material after discharge are called secondary batteries or storage batteries. Among storage batteries, lithium-ion batteries are the most promising and widely used energy storage method, which can be seen from the annual shipment of lithium-ion batteries on the market. This is largely due to the country's advocacy of clean energy and the reality of global warming. However, although the use of energy storage devices (such as lithium-ion batteries) to replace fossil raw materials can reduce greenhouse gas emissions, the energy density of lithium-ion batteries decreases due to the lithium ions consumed during the first charge of the battery, which undoubtedly limits the development of energy storage devices such as lithium-ion batteries.

[0003] The above defects are worth solving. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the present invention provides a composite conductive functional film and a preparation method thereof.

[0005] The technical solution of the present invention is as follows:

[0006] A composite conductive functional film, characterized in that it comprises a first film substrate layer, a second film substrate layer and a mixed layer arranged between the first film substrate layer and the second film substrate layer,

[0007] The mixed layer comprises a thin film layer, on which a plurality of parallel rows of indentations are arranged, and the indentations are filled with a lithium supplement layer;

[0008] A high temperature resistant sponge layer is provided between the mixed layer and the second film substrate layer;

[0009] The surfaces of the first film substrate layer and the second film substrate layer are both provided with a metal layer.

[0010] The present invention according to the above scheme is characterized in that the thickness of the first film substrate layer and the second film substrate layer are both 1-2 μm.

[0011] The present invention according to the above scheme is characterized in that the thickness of the mixed layer is 500-1000nm.

[0012] The present invention according to the above scheme is characterized in that an organic thin film layer is provided on the surface of the mixed layer, and the high temperature resistant sponge is connected to the mixed layer through the organic thin film layer.

[0013] Furthermore, the organic thin film layer is formed by coating an organic lithium salt dissolved in a lipid solvent.

[0014] Furthermore, the organic lithium salt is any one of lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.

[0015] Furthermore, the lipid solvent is any one of ethyl acetate, dimethyl carbonate, and n-butyl acetate.

[0016] The present invention according to the above scheme is characterized in that the metal layer includes a nickel-copper alloy layer and a copper layer located on the surface of the nickel-copper alloy layer.

[0017] On the other hand, a method for preparing the composite conductive functional film as described above is characterized by comprising the following steps:

[0018] S1, preparing a first film substrate layer and a film layer, and etching a plurality of side-by-side indentations on the surface of the film layer;

[0019] S2, filling lithium metal into the indentation to form a mixed layer;

[0020] S3, coating the surface of the mixed layer with an organic thin film layer so that it covers the surface of the lithium metal;

[0021] S4, compounding a high temperature resistant sponge layer on the surface of the organic film layer;

[0022] S5, compounding the second film substrate layer onto the surface of the high temperature resistant sponge layer;

[0023] S6, respectively adding a metal layer on the surface of the first film substrate layer and the surface of the second film substrate layer;

[0024] S7. Complete the preparation of the composite conductive functional film.

[0025] The present invention according to the above scheme is characterized in that, after step S5, a lamination step is also included, in which the composited film structures are rolled to reduce the overall thickness.

[0026] The present invention according to the above scheme has the beneficial effect that, by arranging a mixed layer between two thin film substrate layers, the mixed layer includes a thin film layer and a lithium replenishing layer arranged at intervals, and covering the surface of the lithium replenishing layer with a high temperature resistant sponge, the lithium ions consumed by the SEI film generated by the first charging of the battery can be replenished to the lithium ion battery, thereby improving the energy density of the lithium ion battery. Compared with traditional lithium replenishing methods, such as lithium foil replenishing, the present invention has higher safety performance. Moreover, by using the same equipment as that for plating the metal layer on the first thin film substrate layer and the second thin film substrate layer to arrange the lithium metal in the dent, there is no need to use additional equipment to achieve the above operation, which also greatly reduces the cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a structural schematic diagram of the present invention.

[0028] In the figure, 1 is a metal layer; 2 is a first thin film substrate layer; 31 is a thin film layer; 32 is a lithium supplement layer; 4 is an organic thin film layer; 5 is a high temperature resistant sponge layer; and 6 is a second thin film substrate layer. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with the accompanying drawings and embodiments:

[0030] like Figure 1 As shown, a composite conductive functional film includes a first film substrate layer 2, a second film substrate layer 6, and a mixed layer arranged between the first film substrate layer 2 and the second film substrate layer 6.

[0031] The surfaces of the first film substrate layer 2 and the second film substrate layer 6 are both provided with a metal layer 1. The metal layer 1 includes a nickel-copper alloy layer and a copper layer located on the surface of the nickel-copper alloy layer. The nickel-copper alloy layer as the first metal layer is used to ensure the bonding strength between the metal layer 1 and the first film substrate 2 and the second film substrate layer 6. The copper layer is then coated on the periphery for reinforcement to ensure the physical and chemical stability of the product.

[0032] Preferably, the thickness of the nickel-copper alloy layer is 30-100 nm, and the thickness of the copper layer is 500-1000 nm. In the lamination process, the copper layer can first be plated with a copper film by magnetron sputtering, and then the copper film thickness can be increased by a water plating device to form the final copper layer.

[0033] The thickness of the first film substrate layer 2 and the second film substrate layer 6 in the present invention are both 1-2 μm, which ensures the stability of the composite conductive functional film while ensuring the stability of the product structure.

[0034] The mixed layer includes a thin film layer 31 and a lithium supplement layer 32. The thin film layer 31 is provided with a plurality of parallel rows of indentations (not shown in the figure, the same below) at a certain distance, and lithium metal is filled in the indentations to form the lithium supplement layer 32. After the lithium metal is filled, a complete mixed layer is obtained. The lithium metal in the lithium supplement layer 32 is a lithium source for the lithium ion battery, which supplements the lithium ions consumed by the lithium ion battery due to the first charge, etc.

[0035] The thickness of the mixed layer in the present invention is 500-1000 nm.

[0036] A high temperature resistant sponge layer 5 is provided between the mixed layer and the second film substrate layer 6, and an organic film layer 4 is provided on the surface of the mixed layer, and the high temperature resistant sponge 5 is connected to the mixed layer through the organic film layer 4. The organic film layer 4 is placed between the mixed layer and the high temperature resistant sponge layer 5 to protect the metallic lithium (i.e., the lithium replenishing layer 32) from being oxidized during transportation or production, and the organic film layer 4 will also dissolve after contacting the electrolyte, and will not hinder the lithium replenishing layer 32 from contributing lithium ions.

[0037] The organic film layer 4 is formed by coating an organic lithium salt dissolved in a lipid solvent. The organic lithium salt is any one of lithium bis(oxalatoborate), lithium difluoro(oxalatoborate), lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide; the lipid solvent is any one of ethyl acetate, dimethyl carbonate and n-butyl acetate. Preferably, in the organic film layer, the mass proportion of the organic lithium salt is 40-60%, so that the organic film can be effectively dissolved after encountering the electrolyte.

[0038] Preferably, the thickness of the organic thin film layer is 20-50 nm.

[0039] After the first film substrate layer 2, the second film substrate layer 6, the mixed layer, and the organic film layer 4 are arranged, they are rolled and pressed together before the metal layer is laid.

[0040] Specifically, the preparation method of the composite conductive functional film comprises the following steps:

[0041] S1. Prepare a first film substrate layer and a film layer, and etch a plurality of side-by-side indentations on the surface of the film layer.

[0042] First, a film product with a thickness of 1-2 μm is selected as the first film substrate layer, and a film product with a thickness of 500-1000 nm is selected as the film layer. After the materials are taken, the two are thermally bonded together;

[0043] Secondly, a series of rectangular dents are etched on the thin film product as the thin film layer, and the width of the dents is 100-250nm, the length is consistent with the length of the thin film layer, the height is 500-1000nm, and the interval between two adjacent dents is 30-50nm.

[0044] S2. Fill the indentations with lithium metal to form a mixed layer.

[0045] In the present invention, vacuum coating technology is used to fill lithium metal in the dents formed in step S1 to form a lithium supplement layer. The lithium supplement layer and the thin film layer together constitute a mixed layer.

[0046] S3. Coating an organic thin film layer on the surface of the mixed layer so that it covers the surface of the lithium metal.

[0047] The organic film layer is composed of an organic lithium salt dissolved in a lipid solvent, the organic lithium salt can be any one of lithium bis(oxalatoborate) (LiBOB), lithium difluorooxalatoborate (LiDFOB), lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), and the organic lipid solvent is mainly any one of ethyl acetate, dimethyl carbonate, and n-butyl acetate. Among them, the mass proportion of the organic lithium salt should be 40-60%.

[0048] The organic film is used to protect the metal lithium layer from oxidation during transportation or production. The organic film will also dissolve after contacting the electrolyte and will not hinder the metal lithium layer from contributing lithium ions. The thickness of the organic film layer is 20-50nm.

[0049] S4. Compounding a high temperature resistant sponge layer on the surface of the organic film layer.

[0050] The present invention compounds the high temperature resistant sponge layer to the surface of the organic film layer by means of thermal compounding.

[0051] The main function of the high temperature resistant sponge is to introduce electrolyte from the side so that the electrolyte can infiltrate the entire organic film layer, dissolve the film layer, and thus release the metal lithium ions in the lithium replenishment layer.

[0052] S5, compounding the second film substrate layer onto the surface of the high temperature resistant sponge layer.

[0053] The second film substrate layer is laminated to the surface of the high temperature resistant sponge layer by a film laminating machine to form an outer surface base layer.

[0054] After the first film substrate layer, the second film substrate layer and the internal mixed layer are manufactured, a lamination step is also included, that is, the composite film structures are rolled and laminated to reduce the overall thickness.

[0055] S6, respectively adding a metal layer on the surface of the first film substrate layer and the surface of the second film substrate layer.

[0056] The metal layer includes a nickel-copper alloy metal layer and a copper layer outside the nickel-copper alloy layer. Specifically:

[0057] (1) First, a double-sided continuous vacuum coating method is used to coat a layer of metal on the surface of the first film substrate layer and the surface of the second film substrate layer, respectively, to form a nickel-copper alloy metal layer. Preferably, vacuum coating can be performed by vacuum evaporation or magnetron sputtering.

[0058] Here, nickel-copper alloy is used as the first metal layer because the bonding strength between nickel-copper alloy and the first film substrate layer / the second film substrate layer is higher than that of pure copper. Preferably, the thickness of the nickel-copper alloy can be 30-100 nm.

[0059] (2) Secondly, based on step (1), a layer of metal copper is plated on the surface of the nickel-copper alloy layer by magnetron sputtering, preferably with a thickness of 100-200 nm.

[0060] (3) Finally, a water plating device is used to continue copper plating outside the metal copper layer of step (2) to increase the thickness of copper and form a final copper layer. Preferably, the thickness of the final copper layer is 500-1000nm.

[0061] S7. Complete the preparation of the composite conductive functional film.

[0062] Comparative experiment

[0063] Different experimental examples and comparative examples were selected respectively, and the energy densities of the different experimental examples and comparative examples were tested.

[0064] 1. Assembling the comparative lithium-ion battery

[0065] (1) The positive electrode sheet is composed of a positive electrode current collector and a positive electrode active material coated on the positive electrode current collector. The positive electrode current collector is composed of a 5μm PP film and aluminum metal coated on the PP film, the thickness of the aluminum metal is 1μm, and the positive electrode active material is lithium iron phosphate.

[0066] (2) The negative electrode sheet is composed of a negative electrode current collector and a negative electrode active material coated on the negative electrode current collector, wherein the negative electrode current collector is composed of a 5 μm PP film and metal copper plated on the PP film, the thickness of the metal copper is 1 μm, and the negative electrode active material is graphene.

[0067] (3) The electrolyte of the comparative example is 1 mol / L LiPF6, wherein the volume ratio of PC (propylene carbonate):EC (ethylene carbonate):DMC (dimethyl carbonate) is 10:30:60, and the separator is a polyethylene film;

[0068] (4) Assemble the above components into a button battery in a glove box.

[0069] 2. Lithium-ion battery of the assembly example

[0070] The components and parts of the lithium ion battery are different from those of the battery in the comparative example in that the negative electrode current collector used in the embodiment adopts the composite conductive functional film of the present invention, and the other structural parts are the same as those of the comparative example.

[0071] Select three different examples (i.e., Example 1, Example 2, and Example 3) and three different comparative examples (i.e., Comparative Example 1, Comparative Example 2, and Comparative Example 3). At 25°C, the lithium-ion batteries of each example and comparative example are charged to 3.65V at 0.2C constant current and constant voltage, with a cut-off current of 0.05C; and discharged to 2.5V at 0.2C constant current. The energy density released by the lithium-ion battery core is calculated. The results are shown in Table 1.

[0072] Table 1: Energy density test results comparison table

[0073] Energy density (Wh / kg) Example 1 140.5 Example 2 146.2 Example 3 144.7 Comparative Example 1 128 Comparative Example 2 125.5 Comparative Example 3 123.4

[0074] According to the above comparative experiments, the lithium-ion battery using the composite conductive functional film of the present invention can obtain a better energy density than the traditional lithium-ion battery.

[0075] It should be understood that those skilled in the art can make improvements or changes based on the above description, and all these improvements and changes should fall within the scope of protection of the appended claims of the present invention.

[0076] The above is an exemplary description of the present invention in conjunction with the accompanying drawings. It is obvious that the implementation of the present invention is not limited to the above-mentioned method. As long as various improvements are made by adopting the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A composite conductive functional film, characterized in that: The invention comprises a first film substrate layer, a second film substrate layer and a mixed layer arranged between the first film substrate layer and the second film substrate layer. The mixed layer comprises a thin film layer, on which a plurality of parallel rows of indentations are arranged, and the indentations are filled with a lithium supplement layer; A high temperature resistant sponge layer is provided between the mixed layer and the second film substrate layer, an organic film layer is provided on the surface of the mixed layer, the high temperature resistant sponge is connected to the mixed layer through the organic film layer, and the organic film layer is formed by coating an organic lithium salt dissolved in a lipid solvent; A metal layer is disposed on the surface of the first film substrate layer and the second film substrate layer. The metal layer includes a nickel-copper alloy layer and a copper layer located on the surface of the nickel-copper alloy layer.

2. The composite conductive functional film according to claim 1, characterized in that: The thickness of the first film substrate layer and the second film substrate layer are both 1-2 μm.

3. The composite conductive functional film according to claim 1, characterized in that: The thickness of the mixed layer is 500-1000 nm.

4. The composite conductive functional film according to claim 1, characterized in that: The organic lithium salt is any one of lithium bis(oxalatoborate), lithium difluoro(oxalatoborate), lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.

5. The composite conductive functional film according to claim 1, characterized in that: The lipid solvent is any one of ethyl acetate, dimethyl carbonate and n-butyl acetate.

6. A method for preparing the composite conductive functional film according to any one of claims 1 to 5, characterized in that: The following steps are included: S1, preparing a first film substrate layer and a film layer, and etching a plurality of side-by-side indentations on the surface of the film layer; S2, filling lithium metal into the indentation to form a mixed layer; S3, coating the surface of the mixed layer with an organic thin film layer so that it covers the surface of the lithium metal; S4, compounding a high temperature resistant sponge layer on the surface of the organic film layer; S5, compounding the second film substrate layer onto the surface of the high temperature resistant sponge layer; S6, respectively adding a metal layer on the surface of the first film substrate layer and the surface of the second film substrate layer; S7. Complete the preparation of the composite conductive functional film.

7. The method for preparing the composite conductive functional film according to claim 6, characterized in that: After step S5, a lamination step is also included, in which the composited film structures are rolled to reduce the overall thickness.

Citation Information

Patent Citations

  • Composite conductive functional film

    CN214175709U